Vision for medicine: Staphylococcus aureus biofilm war and unlocking key's for anti-biofilm drug development. (October 2018) - Mohammed, Yasser Hussein Eissa; Manukumar, H.M.; Rakesh, K.P.; Karthik, C.S.; Mallu, P.; Qin, Hua-Li
Abstract: The Staphylococcus aureus biofilm-associated burden is challenging to the field of medicine to eradicate or avoid it. Even though a number of S. aureus biofilm mechanisms understood and established the possible ways of biofilm formation but, still need to know more and require a development of new therapeutic strategies. In this viewpoint, we discuss the underlining biofilm mechanism, its existing systems as active therapeutic agents and as vehicles to transport drugs to the site of infection. The step-back in drug development is due to the emergence of antibiotic-resistant S. aureus . The understanding of bacteria/biofilms is an aspect that we likewise summarize for possible drug development for future as medicine against resistant S. aureus was viewed. Graphical abstract: Highlights: Staphylococcus aureus is one of the major human pathogen cause's mild superficial infections to severe life-threatening invasive infections. The biofilm play an important role in antibiotic drug resistance which leads to public threat globally. In this viewpoint, we discuss the underlining biofilm mechanism, its existing systems as active therapeutic agents and as vehicles to transport drugs to the site of infection. The understanding of bacteria/biofilms is an aspect that we likewise summarize for possible drug development for future as medicine against resistant S. aureus was viewed.